Application Research of ATIS On-board System for High-speed EMUs Based on RFID Technology - WEI Yongquan; ZHANG Yinhuan; ZHOU Jia; DAI Mingxia; SHI Xinyue (机车电传动)
Through analyzing the system composition and working principle of ATIS (Automatic Train Identification System) for common speed trains, the function requirement and system constitution of ATIS on-board system for high-speed EMUs was proposed, and the on-board system topology structure which matching well with all types of vehicle information devices was designed. The data interface, message structure, coding mode, data exchange nexus & interaction mechanism between ATIS on-board equipments and EMUs information devices was designed and analyzed, the ATIS on-board system overall arrangement scheme which fulfilled high-speed EMUs operation demands was contrived, which realized the EMUs attribute information remote online acquisition, and enhanced the transportation organization efficiency.